The development of winter wheat lines with several genes for resistance to Puccinia graminis Pers. f. sp. tritici for use in breeding programs in Russia - I. F. Lapochkina; O. A. Baranova; N. R. Gainullin; G. V. Volkova; E. V. Gladkova; E. O. Kovaleva; A. V. Osipova (Вавиловский журнал генетики и селекции)
The aim of this research is to develop for the Russian Federation Non-Cher nozem Zone competitive prototypes of winter wheat cul tivars with several genes for resistance to stem rust (in clu ding race Ug99) based on new sources of resistance with the use of molecular markers. The individual plants and then lines of winter common wheat with several effective genes for resistance to race Ug99 of stem rust were selected by means of marker assistant selection out of hybrid combinations from the crossing of new donors of resistance to this dangerous disease. The development of initial material was based on the use of new sources of resistance to race Ug99 of stem rust from VIR and “Arsenal” collections. Three accessions of winter wheat (wheat-aegi lops-rye line 119/4-06rw, cv. Donskaya Polukarlikovaya, line GT 96|90 from Bulgaria) and one accession of spring wheat (line 113/00i-4 with genetic material from Aegilops triuncialis), which supplemented and contrasted each other in such economically valuable features as plant height, number of days before heading, resistance to powdery mildew and leaf rust, were selected for hybridization and backcrossing. To accelerate the breeding process, resistant genotypes with Sr genes were selected with the use of molecular markers. As a result the lines of winter common wheat with a set of economically valuable features and the presence of two-four genes for resistance to stem rust in homozygote state were created. The spectrum of the stem rust gene combinations in the created lines differs from the gene combinations in the parental accessions involved in the crossing and is associated with the direction of the selections conducted by the marker assisted selection method. We discovered more than 20 different combinations of the Sr2, Sr22, Sr31, Sr32, Sr36, Sr39, Sr40 and Sr47 genes in winter wheat lines. The combination of Sr22 and Sr32 in homozygote state was most often found. The genotypes with a set of economically valuable features approximating or surpassing the standard cultivar of winter wheat Moskov skaya 39 were selected for further testing in breeding nurseries of the Moscow region. The developed initial material is intended for use in selection of winter wheat cultivars resistant to stem rust in different grain-sowing regions of the Russian Federation. This will serve as a barrier for spread of new races of Puccinia graminis and will raise the resistance of selected cultivars to local populations of stem rust.